1989
DOI: 10.1038/bjc.1989.24
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for breast cancer by oestrogen receptor status: a population-based case-control study

Abstract: Summary Data from a population-based case-control study conducted (Stanford et al., 1986). Complete absence of overlap between risk factors for the two types of breast cancer would provide evidence against a progression from one to the other, while overlap would suggest either that there is a progression or that they are independent outcomes with overlapping aetiologies. The few case-control studies conducted to date (Hildreth et al., 1983;McTiernan et al., 1986;Hislop et al., 1986Hislop et al., , 1988Stanf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 26 publications
6
71
0
Order By: Relevance
“…Consistent with our findings, three of these studies found evidence that late age at first birth was associated with receptor-positive tumours only (Potter et al, 1995;Huang et al, 2000;Cotterchio et al, 2003). Our results on breastfeeding are also consistent with the few previous studies that have addressed this (Hildreth et al, 1983;McTiernan et al, 1986;Cooper et al, 1989;Yoo et al, 1997;Huang et al, 2000;Britton et al, 2002;Cotterchio et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our findings, three of these studies found evidence that late age at first birth was associated with receptor-positive tumours only (Potter et al, 1995;Huang et al, 2000;Cotterchio et al, 2003). Our results on breastfeeding are also consistent with the few previous studies that have addressed this (Hildreth et al, 1983;McTiernan et al, 1986;Cooper et al, 1989;Yoo et al, 1997;Huang et al, 2000;Britton et al, 2002;Cotterchio et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…It has previously been proposed that hormonal breast cancer risk factors ought to be predominantly associated with tumours that express oestrogen (ER) and progesterone (PR) receptors, and less so with receptor-negative tumours (McTiernan et al, 1986;Stanford et al, 1987;Potter et al, 1995;Enger et al, 2000;Ursin et al, 2002). However, the studies that have addressed the effect of reproductive factors on breast tumours of different receptor status have yielded mixed results (Hildreth et al, 1983;McTiernan et al, 1986;Stanford et al, 1987;Cooper et al, 1989;Potter et al, 1995;Yoo et al, 1997;Huang et al, 2000;Britton et al, 2002;Cotterchio et al, 2003).…”
mentioning
confidence: 99%
“…[Stanford et al, 1987] 0.9 (0.6-1. [Cooper et al, 1989] 1.6 e (1.0-2.7) 1.3 (0.7-2.5) 0.95 e (0.7-1.4) 1.3 (0.8-2.0) Manjer [Manjer et al, 2001] Some strong and biologically meaningful associations have been reported, but rarely reproduced, for NAT2 [Ambrosone et al, 1996;Hunter et al, 1997;Millikan et al, 1998a;Morabia et al, 2000b;Delfino et al, 2000;Chang-Claude et al, 2001], NAT1 [Millikan et al, 1998a;Zheng et al, 1999], Cyp1a1 [Ambrosone et al, 1995;Ishibe et al, 1998;Huang et al, 1999], COMT [Millikan et al, 1998b;Thompson et al, 1998;Yim et al, 2001], and BRCA1 and BRCA2 [Brunet et al, 1998;Couch et al, 2001]. With some exceptions, these studies belong to the first generation because they did not separate passive smokers from the nonexposed cohort.…”
Section: Metabolic Susceptibilitymentioning
confidence: 99%
“…Most of these studies were conducted in Western populations as early as 1980s. [1][2][3][4][5] Around the same time, it was also discovered that ER1 tumors that lacked progesterone receptor (PR) expression were less responsive to endocrine therapy compared to tumors that expressed PR. 8 This led to studies in the past decade that looked at the link of various risk factors of breast cancer and combined ER/PR information to better explain the underlying differences between the various subtypes of breast cancer.…”
Section: Uiccmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Numerous studies in the past have looked at differences in etiology and risk factors pertaining to presence or absence of ER-alpha. Most of these studies were conducted in Western populations as early as 1980s.…”
Section: Uiccmentioning
confidence: 99%